Childhood obesity and its complications - Ferreira Vasconcelos, Beatriz; Peixoto Carvalho, Gabriela; Queiroz Ferreira, Letícia; Borges de Paula, Valentina; Guimarães Rodrigues, Iara; Marques Pacheco, Lucivania (Seven Editora, 2023)
Introduction: Childhood obesity is a disease described by excessive accumulation of fat in infants and children. It is given when the Body Mass Index (BMI) is above the recommended for your age. The prevalence of obesity has grown significantly in recent decades in both developed and developing countries. Objective: Therefore, the aim of this study is to analyze the main causes of childhood obesity, as well as to describe the factors associated with this pathology. Methodology: This is a Literature Review study. For the survey of articles in the literature, a search was conducted in the following database: Virtual Health Library. The following descriptors were used to search the articles: pediatric obesity and overweight AND associated factors AND cause and its combinations in Portuguese. Results: The prevalence of obesity in children and adolescents largely reflects the most recent changes in eating patterns and physical inactivity. Urbanization, globalization, increased income, increase in durable consumer goods, among others, contributed to a set of lifestyle changes that directly affected the increase in overweight and obesity in children and adolescents. Associated with overweight is the risk factor for other chronic diseases that, happening at such an early stage of life, may predispose individuals still very young to preventable diseases and complications. Type 2 diabetes mellitus, systemic arterial hypertension, dyslipidemia, gastroesophageal reflux disease, osteoarthritis, orthopedic and postural problems, certain types of cancers in later life, social adjustment problems and depression are some of the diseases associated with childhood obesity. Conclusion: Prevention is the most efficient measure for the control of childhood obesity. Therefore, public health policies associated with educational measures and strategies that promote the incorporation of healthy habits are of great importance.